Additional follow-up telephone counselling and initial smoking relapse: a longitudinal, controlled study. Issue 4 (20th April 2016) - Wu, Lei; He, Yao; Jiang, Bin; Zuo, Fang; Liu, Qinghui; Zhang, Li; Zhou, Changxi
Abstract : Objectives: Smoking cessation services can help smokers to quit; however, many smoking relapse cases occur over time. Initial relapse prevention should play an important role in achieving the goal of long-term smoking cessation. Several studies have focused on the effect of extended telephone support in relapse prevention, but the conclusions remain conflicting. Design and setting: From October 2008 to August 2013, a longitudinal, controlled study was performed in a large general hospital of Beijing. Participants: The smokers who sought treatment at our smoking cessation clinic were non-randomised and divided into 2 groups: face-to-face individual counselling group (FC group), and face-to-face individual counselling plus telephone follow-up counselling group (FCF group). No pharmacotherapy was offered. Outcomes: The timing of initial smoking relapse was compared between FC and FCF groups. Predictors of initial relapse were investigated during the first 180 days, using the Cox proportional hazards model. Results: Of 547 eligible male smokers who volunteered to participate, 457 participants (117 in FC group and 340 in FCF group) achieved at least 24 h abstinence. The majority of the lapse episodes occurred during the first 2 weeks after the quit date. Smokers who did not receive the follow-up telephone counselling (FC group) tended to relapse to smoking earlier than those smokers who received the additional follow-up telephone counselling (FCF group), and the log-rank test was statistically significant (p=0.003). A Cox regression model showed that, in the FCF group, being married, and having a lower Fagerström test score, normal body mass index and doctor-diagnosed tobacco-related chronic diseases, were significantly independent protective predictors of smoking relapse. Conclusions: Within the limitations of this study, it can be concluded that additional follow-up telephone counselling might be an effective strategy in preventing relapse. Further research is still needed to confirm our findings.